SHORT COMMUNICATION: BIOREMEDIASI PADA SISTEM BUDIDAYA PERIKANAN - ANDRI KURNIAWAN (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2012)
Aquaculture is one of the important chain in fisheries bioindustry development. Aquaculture is a production unit that can sustain availability of animal protein of fisheries commodity, both raw materials nor food for consumption. In the implementation, aquaculture system generates considerable organic and anorganic wastes, consisting of metabolism products, residual foods, feces, chemical residues, and others that cause water quality deterioration and disease outbreaks. As a result, aquaculture is considered as a potential polluter and a cause of degradation of the aquatic environment. Bioremediation is an integrated and complex system of environmental management program. It is done by using a macro or microorganism and can also by using some combination of them that specifically target particular pollutants. This short communication attempts to describe and elaborate bioremediation present status and future prospect for sustainability of aquaculture system development